Single Window Search System for Libraries using VuFind - Mandal, Sukumar; Saha, Sujan (Journal of Information and Knowledge, 2024)
The main objective of this study is to develop methods for enhancing the search capabilities of library collections by integrating various technological elements. Implementing this functional enhancement will provide users access to modern services and resources. The single-window search mechanism is created and built on the VuFind open-source discovery tool. The common access window has been created after properly configuring ILS-OPAC Koha, CONTENTdm, Digital Commons, DSpace, EPrints, Fedora, Greenstone, Omeka, and OPUS. It is based on LAMP architecture and uses Apache Solr, Tomcat, and Apache Tika to create indexes for easy document search through VuFind. This study suggests a new way to easily search and collect data from different domain-specific cluster tools using a single interface. This domain-specific framework provides an ideal environment for libraries to develop large-scale library discovery services. The originality of this paper lies in creating a prototype integrated framework to facilitate the easy installation and configuration of VuFind for integrating domain-specific software in both ILS and IDR.